PEMBINAAN PEDAGANG MAKANAN OLAHAN DI LINGKUNGAN SEKOLAH UNTUK MENINGKATKAN KUALITAS MAKANAN BAGI ANAK SEKOLAH DI DESA KESIMAN KERTALANGU, DENPASAR TIMUR - U. Dwipayanti; T. Adhi; A. Wirawan; Sutiari Sutiari; L. Wulandari (Buletin Udayana Mengabdi, 2010)
School-age children require sufficient source of energy to support their growth. Some places in which children get their food are school’s canteens and vendors in the vicinity of the schools. Nutritional contents, additive substances (food coloring and preservatives) and food processing influence the quality of food in such areas. In addition, there are also problems related to diarrheal diseases and food poisonings due to consuming low quality food, not only in Denpasar but also in other areas of Bali. We assisted and supervised food sellers on the application food safety principles and the importance of high quality food at school’s canteens and food vendors surrounding the school areas. The results indicated that the sellers showed a good improvement in knowledge and attitude on the importance of food safety, supported by the results of direct observations in the field. The responses of teachers at Primary School No 17 Kesiman, and the sellers are good, indicated by their active participation in assisting the activities. Coordination with the teachers is required to perform continual monitoring on the cleanliness and quality of food sold at school canteens as well as surrounding areas. This will be expected to prevent food poisoning and diseases, which eventually improves nutrition status of the school-age children.